Adolescent Idiopathic Scoliosis and Pregnancy: An Unsolved Paradigm - Falick-Michaeli, Tal (Global Spine J, 2015)
Study Design Retrospective cohort study with a cross-sectional comparison. Objective To compare the rates of anesthesia prescription and satisfaction with surgery, prevalence and severity of low back pain, prevalence of depression, and sexual dysfunction among pregnant and nonpregnant patients with AIS undergoing correction surgery with pedicle-based systems and healthy woman with a history of pregnancy. Methods Women between the ages of 18 and 40 years who underwent correction surgery for AIS with a pedicle screw system were interviewed regarding pregnancies, child delivery, method of pain control during delivery, and any long-term outcome after delivery. In addition, sexual dysfunction (Female Sexual Distress Scale–Revised [FSDS]), depression (the Beck Depression Assessment Questionnaire), and Scoliosis Research Society 24 (SRS24) questionnaires were administered. Data was compared between patients with AIS without a history of pregnancy and healthy controls. Results Satisfaction with surgery in the AIS pregnant group using the SRS24 questionnaire scored 3.76/5 (p = 0.0047 when compared with nonpregnant AIS group). Six of the 17 of the women with AIS had severe back pain during pregnancy (35%) mandating home treatment or hospitalization. Of the 17 women, 13 complained of a sustained back pain after child delivery (76%) that impacted their life. In the nonscoliosis group, no back pain attributed to pregnancy was reported. The rates of regional anesthesia prescription among pregnant patients with AIS who underwent correction surgery was 30% (5/17), whereas among healthy pregnant women, rates were 100% (6/6). The SRS24 scores in the patients with AIS were 72% (88/120), showing a low score of 3.69/5 in the pain domains (p = 0.0048 when compared with nonpregnant patients with AIS). Depression rates were in the normal range and similar in all groups. FSDS scores, used to assess sexual dysfunction, were 4.02 in the pregnancy group and 5.67 in the nonpregnant group (not significant) and 4.6 in the nonscoliosis control group (not significant). Conclusion Women who underwent scoliosis correction suffered from long-term back pain after pregnancy and had decreased satisfaction with surgery. In addition, anesthesiologists refused epidurals in a large number of these patients. A larger study is needed on the topic.